Transport Studies Of Carboxymethyl Cellulose/Chitosan-Ammonium Bromide Biopolymer Blend Electrolytes As An Ionic Conductor - Nur Hafiza Mr Muhamaruesa; Mohd Ikmar Nizam Mohamad Isa (Penerbit UMT, 2024)
Indexed by SCOPUS